Method for improving material hardness based on laser shock peening technology
After microarc oxidation treatment of the material and spraying the absorbing layer and restraining layer, laser impact enhancement technology is used to solve the problem of excessive thermal damage during the laser impact enhancement process, and the hardness of the material is effectively improved.
Patent Information
- Application Number
- CN202411920814.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
When using laser impact strengthening technology to modify the surface of the material to improve the hardness of the material, there are problems of excessive thermal damage and deformation, resulting in poor hardness improvement effect.
After performing microarc oxidation treatment on the reinforced material and spraying the absorbing layer and restraining layer on its surface, laser impact strengthening technology is used. The specific steps include placing the material in an acidic solution for microarc oxidation treatment, followed by spraying modified silicon carbide as an absorbing layer and K9 glass as a restraining layer, and finally performing laser impact strengthening.
It effectively avoids excessive thermal damage and deformation during laser impact strengthening, and significantly improves the hardness of the material.
Smart Images

Figure BDA0005207931390000041 
Figure BDA0005207931390000051 
Figure BDA0005207931390000052
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser shock peening surface modification, and in particular to a method for improving material hardness based on laser shock peening technology. Background Art
[0002] Hardness refers to the ability of a material to resist local plastic deformation caused by mechanical indentation or wear. The hardness of a material is one of the important indicators for measuring material quality, and has a vital impact on the service life, performance and quality of various mechanical equipment and industrial products. Therefore, how to improve the hardness of a material has become a research hotspot for technicians in this field. Existing studies have found that appropriate surface treatment of the material surface can effectively improve the hardness of the material.
[0003] Laser shock peening technology is an emerging surface treatment technology that uses the plasma shock mechanics effect induced by a high-power density, low-pulse width laser beam to modify the material surface. Compared with traditional surface treatment technologies such as hardening and quenching, laser shock peening technology has almost no thermal effect on the material surface and has significant advantages such as cleanliness, environmental protection, high operating efficiency and strong controllability.
[0004] However, with the practical application of laser strengthening technology, when using laser strengthening technology to modify the material surface to improve the hardness of the material, a large amount of energy is required to generate the laser beam, and the energy of the laser beam has a certain spatial non-uniformity, which will cause excessive thermal damage and deformation on the material surface, which is not conducive to improving the hardness of the material.
[0005] Therefore, improving the laser strengthening technology and developing a laser strengthening technology solution that can effectively improve the hardness of the material by effectively avoiding excessive thermal damage and deformation has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a method for improving the hardness of a material based on laser shock peening technology, which can effectively improve the hardness of the material by effectively avoiding excessive thermal damage and deformation.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for improving the hardness of a material based on laser shock peening technology comprises the following steps:
[0009] 1) placing the material to be strengthened in an acidic solution and performing micro-arc oxidation treatment on the material to be strengthened;
[0010] 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are sprayed uniformly on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is subjected to laser shock strengthening.
[0011] Furthermore, in step 1), the acidic solution is prepared by mixing hydrochloric acid and phosphoric acid in a volume ratio of (2-3):1.
[0012] Furthermore, the concentration of the hydrochloric acid is 0.1 mol·L -1 .
[0013] Furthermore, the concentration of the phosphoric acid is 0.05 mol·L -1 .
[0014] Furthermore, in step 1), the parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time is 5 to 20 minutes.
[0015] Furthermore, in step 2), the absorption layer is modified silicon carbide.
[0016] Furthermore, the preparation method of the modified silicon carbide includes the following steps: mixing silicon carbide and ferrosoferric oxide in a mass ratio of (5-10) : 1, calcining at 600-800°C for 10 minutes to obtain the modified silicon carbide.
[0017] Furthermore, in step 2), the absorption layer has a thickness of 20 μm to 40 μm.
[0018] Furthermore, in step 2), the constrained layer is K9 glass.
[0019] Furthermore, in step 2), the thickness of the constrained layer is 5 mm.
[0020] Furthermore, in step 2), the parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a method for improving the hardness of a material based on laser shock peening technology. The material surface is first subjected to micro-arc oxidation treatment and then subjected to laser shock peening, thereby effectively avoiding excessive thermal damage and deformation during the shock peening process and effectively improving the hardness of the material. DETAILED DESCRIPTION
[0023] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0024] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] In the following embodiment, a method for improving the hardness of a material based on laser shock peening technology includes the following steps:
[0029] 1) placing the material to be strengthened in an acidic solution and performing micro-arc oxidation treatment on the material to be strengthened;
[0030] Wherein, the acidic solution is composed of a concentration of 0.1 mol·L -1 The concentration of hydrochloric acid is 0.05 mol·L -1 Phosphoric acid is mixed in a volume ratio of (2-3):1;
[0031] The parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time 5 to 20 minutes;
[0032] 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are uniformly sprayed on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is subjected to laser shock strengthening;
[0033] Wherein, the absorption layer is modified silicon carbide;
[0034] The preparation method of the modified silicon carbide comprises the following steps: mixing silicon carbide and ferroferric oxide in a mass ratio of (5-10) to 1, and calcining at 600-800° C. for 10 min to obtain the modified silicon carbide;
[0035] Wherein, the thickness of the absorption layer is 20 μm to 40 μm;
[0036] Wherein, the constrained layer is K9 glass;
[0037] Wherein, the thickness of the constrained layer is 5 mm;
[0038] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0039] In the following embodiments, titanium alloy TC4 is used as an example for laser shock strengthening. Those skilled in the art can refer to the method described in the present invention to perform laser shock strengthening on any material to be strengthened.
[0040] Examples 1 to 6
[0041] A method for improving material hardness based on laser shock peening technology
[0042] 1) Placing titanium alloy TC4 in an acidic solution and subjecting the material to be strengthened to micro-arc oxidation treatment;
[0043] Wherein, the acidic solution is composed of a concentration of 0.1 mol·L -1 The concentration of hydrochloric acid is 0.05 mol·L -1 The phosphoric acid is mixed according to the volume ratio recorded in Table 1;
[0044] Table 1 Volume ratio of hydrochloric acid and phosphoric acid
[0045]
[0046]
[0047] The parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time 5min;
[0048] 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are uniformly sprayed on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is subjected to laser shock strengthening;
[0049] Wherein, the absorption layer is modified silicon carbide;
[0050] The preparation method of the modified silicon carbide comprises the following steps: mixing silicon carbide and ferrosoferric oxide at a mass ratio of 5:1, and calcining at 700°C for 10 minutes to obtain the modified silicon carbide;
[0051] Wherein, the thickness of the absorption layer is 20 μm;
[0052] Wherein, the constrained layer is K9 glass;
[0053] Wherein, the thickness of the constrained layer is 5 mm;
[0054] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0055] The hardness of titanium alloy TC4 after laser shock strengthening in Examples 1 to 6 was tested, and the hardness test results are shown in Table 2;
[0056] Table 2 Hardness test results
[0057]
[0058] It can be seen from the data in Table 2 that during the micro-arc oxidation treatment, using hydrochloric acid and phosphoric acid in different volume ratios as electrolytes will affect the hardness of titanium alloy TC4. Within the test range of 2:1 to 3:1, the hardness of titanium alloy TC4 shows a trend of first increasing and then decreasing, and reaches the optimal hardness at 2.4:1. Therefore, the volume ratio of hydrochloric acid and phosphoric acid is preferably 2.4:1.
[0059] Embodiments 7 to 9
[0060] A method for improving material hardness based on laser shock peening technology
[0061] 1) Placing titanium alloy TC4 in an acidic solution and subjecting the material to be strengthened to micro-arc oxidation treatment;
[0062] Wherein, the acidic solution is composed of a concentration of 0.1 mol·L -1 The concentration of hydrochloric acid is 0.05 mol·L -1 The phosphoric acid is mixed in a volume ratio of 2.4:1;
[0063] The parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time is shown in Table 3;
[0064] Table 3 Micro-arc oxidation treatment oxidation time
[0065]
[0066] 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are uniformly sprayed on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is laser shock strengthened;
[0067] Wherein, the absorption layer is modified silicon carbide;
[0068] The preparation method of the modified silicon carbide comprises the following steps: mixing silicon carbide and ferrosoferric oxide at a mass ratio of 5:1, and calcining at 700°C for 10 minutes to obtain the modified silicon carbide;
[0069] Wherein, the thickness of the absorption layer is 20 μm;
[0070] Wherein, the constrained layer is K9 glass;
[0071] Wherein, the thickness of the constrained layer is 5 mm;
[0072] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0073] The hardness of the titanium alloy TC4 after laser shock strengthening in Examples 7 to 9 was tested, and the hardness test results are shown in Table 4;
[0074] Table 4 Hardness test results
[0075]
[0076] It can be seen from the data in Table 4 that during the micro-arc oxidation treatment process, different micro-arc oxidation treatment oxidation times will affect the hardness of titanium alloy TC4. Within the test range of 5 to 20 minutes, the hardness of titanium alloy TC4 shows a trend of first increasing and then decreasing, and reaches the optimal hardness at 15 minutes. Therefore, the micro-arc oxidation treatment oxidation time is preferably 15 minutes.
[0077] Embodiments 10 to 14
[0078] A method for improving material hardness based on laser shock peening technology
[0079] 1) Placing titanium alloy TC4 in an acidic solution and subjecting the material to be strengthened to micro-arc oxidation treatment;
[0080] The acidic solution is prepared by mixing hydrochloric acid with a concentration of 0.1 mol·L-1 and phosphoric acid with a concentration of 0.05 mol·L-1 in a volume ratio of 2.4:1.
[0081] The parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time 10min;
[0082] 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are uniformly sprayed on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is laser shock strengthened;
[0083] Wherein, the absorption layer is modified silicon carbide;
[0084] The preparation method of the modified silicon carbide comprises the following steps: mixing silicon carbide and ferroferric oxide according to the mass ratio of silicon carbide to ferroferric oxide recorded in Table 5, and calcining at 700° C. for 10 min to obtain the modified silicon carbide;
[0085] Table 5 Mass ratio of silicon carbide and ferroferric oxide
[0086]
[0087]
[0088] Wherein, the thickness of the absorption layer is 20 μm;
[0089] Wherein, the constrained layer is K9 glass;
[0090] Wherein, the thickness of the constrained layer is 5 mm;
[0091] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0092] The hardness of the titanium alloy TC4 after laser shock strengthening in Examples 10 to 14 was tested, and the hardness test results are shown in Table 6;
[0093] Table 6 Hardness test results
[0094]
[0095] It can be seen from the data in Table 6 that the absorption layer prepared with different mass ratios of silicon carbide and ferroferric oxide will affect the hardness of titanium alloy TC4. Within the test range of 5:1 to 10:1, the hardness of titanium alloy TC4 shows a trend of first increasing and then decreasing, and reaches the optimal hardness at 9:1. Therefore, the mass ratio of silicon carbide and ferroferric oxide is preferably 9:1.
[0096] Embodiments 15 to 18
[0097] A method for improving material hardness based on laser shock peening technology
[0098] 1) Placing titanium alloy TC4 in an acidic solution and subjecting the material to be strengthened to micro-arc oxidation treatment;
[0099] The acidic solution is prepared by mixing hydrochloric acid with a concentration of 0.1 mol·L-1 and phosphoric acid with a concentration of 0.05 mol·L-1 in a volume ratio of 2.4:1.
[0100] The parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time 10min;
[0101] 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are uniformly sprayed on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is subjected to laser shock strengthening;
[0102] Wherein, the absorption layer is modified silicon carbide;
[0103] The preparation method of the modified silicon carbide comprises the following steps: mixing silicon carbide and ferroferric oxide at a mass ratio of 9:1, and calcining at 700°C for 10 minutes to obtain the modified silicon carbide;
[0104] Wherein, the thickness of the absorption layer is shown in Table 7;
[0105] Table 7 Thickness of the absorption layer
[0106]
[0107] Wherein, the constrained layer is K9 glass;
[0108] Wherein, the thickness of the constrained layer is 5 mm;
[0109] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0110] The hardness of titanium alloy TC4 after laser shock strengthening in Examples 15 to 18 was tested, and the hardness test results are shown in Table 8;
[0111] Table 8 Hardness test results
[0112]
[0113] It can be seen from the data in Table 8 that the thickness of the absorption layer will affect the hardness of the titanium alloy TC4. In the test range of 20μm to 40μm, the hardness of the titanium alloy TC4 shows a trend of first increasing and then decreasing, reaching the optimal hardness at 30μm, so the thickness of the absorption layer is preferably 30μm.
[0114] In addition, the present invention also uses β-type titanium alloy, austenitic stainless steel and other materials as materials to be strengthened for laser shock strengthening. It has been verified that no matter what kind of material is used, in the process of micro-arc oxidation treatment, hydrochloric acid and phosphoric acid are mixed in a volume ratio of 2.4:1 as an electrolyte, and the micro-arc oxidation treatment is performed for 15 minutes. In the process of laser shock strengthening, silicon carbide and ferrosoferric oxide are used to prepare an absorption layer in a mass ratio of 9:1, and the thickness of the absorption layer is controlled to be 30μm, which can most effectively improve the hardness of the material.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for improving material hardness based on laser shock peening technology, characterized in that: The following steps are involved: 1) placing the material to be strengthened in an acidic solution and performing micro-arc oxidation treatment on the material to be strengthened; 2) After the micro-arc oxidation treatment in step 1 is completed, an absorption layer and a constraint layer are sprayed uniformly on the surface of the material to be strengthened in sequence, and the surface of the material to be strengthened is subjected to laser shock strengthening.
2. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 1), the acidic solution is prepared by mixing hydrochloric acid and phosphoric acid in a volume ratio of (2-3):
1.
3. The method for improving material hardness based on laser shock peening technology according to claim 2, characterized in that: The concentration of the hydrochloric acid is 0.1 mol·L -1 ; The concentration of the phosphoric acid is 0.05 mol·L -1 .
4. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 1), the parameters of the micro-arc oxidation treatment are: frequency 500 Hz, duty cycle 30%, current density 5A·dm -2 , oxidation time is 5 to 20 minutes.
5. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 2), the absorption layer is modified silicon carbide.
6. The method for improving material hardness based on laser shock peening technology according to claim 5, characterized in that: The preparation method of the modified silicon carbide comprises the following steps: mixing silicon carbide and ferrosoferric oxide in a mass ratio of (5-10) to 1, and calcining at 600-800° C. for 10 minutes to obtain the modified silicon carbide.
7. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 2), the thickness of the absorption layer is 20 μm to 40 μm.
8. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 2), the constrained layer is K9 glass.
9. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 2), the thickness of the constrained layer is 5 mm.
10. The method for improving material hardness based on laser shock peening technology according to claim 1, characterized in that: In step 2), the parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.